2018
DOI: 10.1021/acs.inorgchem.8b01788
|View full text |Cite
|
Sign up to set email alerts
|

Intriguing Structural Transition Inducing Variable Birefringences in ABa2MS4Cl (A = Rb, Cs; M = Ge, Sn)

Abstract: A suite of quinary thiohalides, ABaMSCl (A = Rb, Cs; M = Ge, Sn), have been successfully synthesized. ABaMSCl (A = Rb, Cs; M = Ge, Sn) undergoes an interesting structural transition from P2/ c (α phase) to I4/ mcm (β phase), which also leads to obvious disparities on the birefringence from 0.041 (α phase) to 0.094 (β phase). Moreover, the result of deploying a real-space atom-cutting method on ABaMSCl reveals that their (MS) groups may take the major effect in terms of the anisotropy by a structural transition. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 47 publications
2
29
0
Order By: Relevance
“…33 Such a value is significantly greater than those of commercially available birefringent materials, such as YVO 4 (Δn = 0.225 at 630 nm), 4 α-BaB 2 O 4 (Δn = 0.122 at 544 nm), 5 and LiNbO 3 (Δn = 0.083 at 632 nm). 2 It is also evidently larger than those of the newly reported chalcogenides and the emerging lone-pair cation-based birefringent crystals, such as β-CsBa 2 SnSe 4 Cl (0.14 at 532 nm), 34 Cs 2 ZnSn 3 S 8 (0.12 at 546 nm), 35 Rb 3 NaSn 3 Se 8 , (0.196 in the visible region), 36 LiBaSbS 3 (0.045 at 532 nm), 10b and Sn 2 B 5 O 9 Cl (0.168 at 546 nm). 6c To the best of our know ledge, the experimental Δn value of CsCu 3 SbS 4 is the highest among metal chalcogenides reported thus far.…”
mentioning
confidence: 90%
“…33 Such a value is significantly greater than those of commercially available birefringent materials, such as YVO 4 (Δn = 0.225 at 630 nm), 4 α-BaB 2 O 4 (Δn = 0.122 at 544 nm), 5 and LiNbO 3 (Δn = 0.083 at 632 nm). 2 It is also evidently larger than those of the newly reported chalcogenides and the emerging lone-pair cation-based birefringent crystals, such as β-CsBa 2 SnSe 4 Cl (0.14 at 532 nm), 34 Cs 2 ZnSn 3 S 8 (0.12 at 546 nm), 35 Rb 3 NaSn 3 Se 8 , (0.196 in the visible region), 36 LiBaSbS 3 (0.045 at 532 nm), 10b and Sn 2 B 5 O 9 Cl (0.168 at 546 nm). 6c To the best of our know ledge, the experimental Δn value of CsCu 3 SbS 4 is the highest among metal chalcogenides reported thus far.…”
mentioning
confidence: 90%
“…[11][12][13] In the past few decades, a large number of chalcohalides have been developed, such as (A 3 X) [MB 12 (MS 4 ) 3 ] (A = K, Cs; X = Cl, Br, I; M = Ga, In, Gd), 14 [ABa 3 Cl 2 ][Ga 5 S 10 ] (A = K, Rb, and Cs), 15 Na 2 GaS 2 Cl 16 and ABa 2 MS 4 Cl (A = Rb, Cs; M = Ge, Sn). 17 Metal chalcogenides with low bandgaps are widely implemented in solar cells and wide bandgap materials are transparent in infrared region, which is especially fit for infrared optics. [18][19][20][21][22] In this regard, the exploration of new metal chalcohalides with unique structures and properties is considerably significant.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21] Recently, a great number of alkali-and/or alkaline earthmetal chalcogenides with wide band gaps have been developed by high temperature solid-state reactions. 22,23 For example, in 2008 Ye et al reported the fabrication of IR NLO material BaGa 4 S 7 , 24 which exhibited a large band gap, high LIDT, wide optically transparent region, and suitable second-order susceptibility coefficients. After that, in 2010, Wu, Yao and coworkers reported the fabrication of α-BaGa 4 Se 7 with enhanced NLO coefficients compared with BaGa 4 S 7 .…”
Section: Introductionmentioning
confidence: 99%